Sustainability Consciousness Dimensions for Achieving Sustainability Performance in Thailand: Role of Supply Chain Resilience - Khajornsak Thaiprayoon; Maneerat Mitprasat; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
Organization can never achieve sustainability until its employees not develop such consciousness about sustainability. Such consciousness includes knowingness, attitude and behavior regarding sustainability which can affect sustainability performance. This research has seen the impact of supply chain resilience on sustainability performance in mediating role of sustainability consciousness in Thailand’s manufacturing sector. Managerial employees have been taken as unit of analysis as data has been collected from them through questionnaire. Respective data was then analyzed by applying CFA and SEM through AMOS and data screening through SPSS. Results have confirmed that supply chain resilience has significant impact on sustainability performance through sustainability consciousness dimensions. This study is unique and novel due to adding sustainability performance as new outcome of resilience driven sustainability consciousness. Implications of this study will add empirical evidence about sustainability consciousness and performance linkage and will also facilitate Thailand’s manufacturing industry to train their employees to develop sustainability consciousness in them. Future research indications and limitations have also been given in this study.